FACTORS CONTRIBUTING TO EMPLOYEE - Cawe, Mawethu (My University, 2011)
Employee engagement is a critical business issue for South Africa if we are to take this country to the next competitive landscape. South African business has been mired by negative perception of underperformance and uncompetitiveness from the international community for years in the past, with an over-reliance on the mining sector. From 1994, this perception has progressively improved and going forward more urgency from business is required in order to progress even further. Whilst employee engagement represents only one factor amongst a number of macro and micro issues, it is central to this country’s economy, business productivity and sustainability. In attempting to assist business in this regard, a study of factors that promote employee engagement has been investigated. The research was qualitative and quantitative in nature. A number of respondents from across the length and breath of South Africa participated in the study. Analysis was done on the results and correlation done to the propositions and the literature. The findings identified employee engagement strategy, the culture of engagement, leadership and management, talent mindset, communication and knowledge sharing, and organisations’ reputation and branding as prominent factors in business in South Africa. Resulting from the research, an employee engagement model is proposed which attempts to integrate key lessons for business.
MM - P&DM
Keywords: Employee engagement; Talent management; Human resources